Changes in pathophysiology of tumor growth and functional activity of the hypothalamic-pituitary-thyroid axis in rats of both sexes with the development of Guerin's carcinoma on the background of hypothyroidism - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; E. I. Surikova; I. V. Neskubina; Yu. A. Pogorelova; L. K. Trepitaki; N. D. Cheryarina; L. A. Nemashkalova; A. Yu. Arakelova (Южно-Российский онкологический журнал, 2022)
Purpose of the study. Was to analyze changes in pathophysiological parameters of transplantable tumor growth and functional activity of the hypothalamic-pituitary-thyroid axis (HPT) in rats of both sexes with Guerin's carcinoma in presence of induced hypothyroidism.Materials and methods. The dynamics of tumor growth and average life span were assessed in white alley rats of both sexes with Guerins carcinoma transplanted subcutaneously on the background of thyreostatic induced hypothyroidism. RIA (radioimmune assay) and ELISA (enzyme-linked immunosorbent assay) methods were used to determine levels of thyroid hormones in the blood and thyroid and tumor samples, and thyrotropin-releasing hormone (TRH) in the hypothalamus, as well as TSH in the pituitary gland. The experiment included 2 control groups: animals of both sexes with hypothyroidism (control group 1, number of rodents = 15) and animals with subcutaneously transplanted Guerin's carcinoma without hypothyroidism (control group 2, number of rodents = 15).Results. Hypothyroidism in female rats inhibited the tumor growth and improved median survival by 1.8 times (p < 0.05). No such effect was observed in males of the main group. Levels of regulatory peptides of the hypothalamus and pituitary gland declined in females of the main group, while levels of TSH in the pituitary gland in males increased, despite a decrease in TRH by 3.5 times. TSH levels decreased in the thyroid and blood of animals of both sexes; however, a decrease in levels of total and free circulating thyroxine (T4 and FT4) by 1.6 times and by 2.8 times was found in the tumor, respectively; samples of Guerin's carcinoma in males of the main group remained saturated with T4 and FT4 as well as and in control group rodents without induced hypothyroidism.Conclusions. The gender differences in the pathophysiology of the tumor development in presence of hypothyroidism, as well as changes in the functional activity of the HPT axis in experimental animals revealed in this study can probably be associated with sex hormones, which requires further study of the hypothalamic-pituitary-gonadal (HPG) axis and steroid hormones in peripheral organs and tumor samples.